Comparative Performance Analysis of 4 Different Anti-Citrullinated Protein Assays in the Diagnosis of Rheumatoid Arthritis - (:unkn) unknown (J RHEUMATOL PUBL CO, 2009)
Objective. To evaluate the diagnostic performances of 2 recently developed assays, third-generation anti-cyclic citrullinated peptide(anti-CCP3) and anti-mutated citrullinated vimentin (anti-MCV), in comparison to conventional second-generation anti-cyclic citrullinated peptide (anti-CCP2) assay; and to assess a novel fully automated, random-access AxSYM anti-CCP assay for early diagnosis of rheumatoid arthritis (RA). Methods. A cohort of 176 patients was enrolled in our study; 93 were diagnosed as having RA. The non-RA group consisted of 83 patients including 38 with Systemic lupus erythematosus, 17 with primary Sjogren's syndrome, 11 with osteoarthritis, and 17 healthy controls. All were tested for presence of anti-CCP2, anti-CCP3, AxSYM anti-CCP, anti-MCV, and rheumatoid factor (RF)-IgM according to the manufacturers' instructions. Results. Diagnostic performance of the assays revealed the highest area under the Curve for the novel AxSYM anti-CCP [89.1; 95% confidence interval (CI) 84.3-93.8], followed by anti-CCP3 (86.7; 95% CI 81.6-91.9), anti-CCP2 (82; 95% CI 75.8-88.3), and anti-MCV (71.9 95% CI 64.4-79.5). The sensitivities and specificities were 60.2% and 98.8% for anti-CCP2, 61.3% and 97.6% for anti-CCP3, 80.6% and 84.3% for AxSYM anti-CCP 49.8% and 91.6% for anti-MCV, and 67.8% and 91.6% for RF-IgM, respectively. Conclusion. At cutoff of 5 U/ml, AxSYM anti-CCP emerged as a highly sensitive first-line early diagnostic tool for RA, with the greatest discrimination power, above 16 U/ml, in case of positive result. Using a single easily performed automated assay at 2 determined decision limits we were able to diagnose 81% of cases of RA and missing only 1.2%. (First Release Feb 15 2009; J Rheumatol 2009;36:491-500; doi: 10.3899/jrheum.080656)
Keywords: AUTOMATION; CYCLIC CITRULLINATED PEPTIDE AUTOANTIBODIES; DIFFERENTIATION; DIAGNOSIS; EARLY RHEUMATOID ARTHRITIS; MUTATED CITRULLINATED VIMENTIN; CLASSIFICATION CRITERIA; REVISED CRITERIA; PEPTIDE ANTIBODIES; VIMENTIN; 2ND-GENERATION; PREDICTION; ACCURACY